2000
DOI: 10.1097/00006254-200004000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Breast Feeding and Asthma in 6 Year Old Children: Findings of a Prospective Birth Cohort Study

Abstract: (Accepted 2 June 1999)Association between breast feeding and asthma in 6 year old children: findings of a prospective birth cohort study W H Oddy, P G Holt, P D Sly, A W Read, L I Landau, F J Stanley, G E Kendall, P R Burton AbstractObjectives To investigate the association between the duration of exclusive breast feeding and the development of asthma related outcomes in children at age 6 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
152
1
5

Year Published

2001
2001
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(168 citation statements)
references
References 18 publications
10
152
1
5
Order By: Relevance
“…No association was found in this study between breastfeeding and the prevalence of symptoms of wheeze and rhinoconjunctivitis. The ®ndings are in agreement with previous observations [14, 21±23], but at variance with two cohort studies showing a protective association between breastfeeding and asthma [15,16] and the Tokorozawa Childhood Asthma and Pollinosis Study of Japanese schoolchildren, which showed that breastfeeding was signi®cantly associated with an increased prevalence of asthma [17]. Both Suita City and Tokorozawa City are suburban residential cities.…”
Section: Discussionsupporting
confidence: 92%
“…No association was found in this study between breastfeeding and the prevalence of symptoms of wheeze and rhinoconjunctivitis. The ®ndings are in agreement with previous observations [14, 21±23], but at variance with two cohort studies showing a protective association between breastfeeding and asthma [15,16] and the Tokorozawa Childhood Asthma and Pollinosis Study of Japanese schoolchildren, which showed that breastfeeding was signi®cantly associated with an increased prevalence of asthma [17]. Both Suita City and Tokorozawa City are suburban residential cities.…”
Section: Discussionsupporting
confidence: 92%
“…One aspect of this study contributes important new insight into this issue, as follows. Previous cohort studies that have provided the strongest statistical support for a causative role for the cumulative (potentially synergistic) effects of infection-induced and atopy-induced airways inflammation in the etiology of persistent asthma in childhood 20,25,28 have suffered from the limitation of lack of information on the timing of atopic sensitization among respective study groups. In both cases, these studies have relied on assessment of atopy status at outcome age (5 or 6 years), which is several years beyond the peak period of respiratory viral infections during infancy.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously reported synergistic interactions between atopic sensitization and recurrent respiratory infections in early life on the risk of asthma. 20 We therefore hypothesised that this risk would be conferred by sensitization early in life rather than later sensitization.…”
Section: Abbreviations Usedmentioning
confidence: 99%
“…Breastfeeding, the optimal source of infant nutrition, has been shown to protect the infant against infectious diseases [1][2][3], obesity [4] and several chronic illnesses [5,6] including allergic symptoms, especially childhood asthma [7,8]. However, studies on the effects of breastfeeding on the development of allergy have yielded controversial results, some studies indicating an allergypreventive effect [9][10][11], while other studies have been unable to confirm such an effect [12][13][14], or the protective effect has been limited to early childhood, long-term follow-up indicating increased atopic symptoms among the breastfed subjects [15][16][17]. In a large cluster-randomized trial, an intervention promoting breastfeeding decreased the risk of atopic eczema during the first year of life [18].…”
Section: Introductionmentioning
confidence: 99%